Evaluating the impact of computer accounting media applications on human development - Listiadi, Agung; Rochmawati (Nurture, 2024)
Purpose: Technology in education especially in accounting and computer learning is currently needed to support teacher performance and as a facility for students to participate in the learning process in the 21st century. This study aimed to determine whether there are differences in the performance of teachers before and after training on information technology-based learning evaluation models that use accounting applications. Design/Methodology/Approach: The process of mastering Wondershare software is carried out for economics and accounting teachers in order to enhance the quality of learning. The research design uses a true pre-and post-tests experimental design with respondents being teachers in the field of accounting learning. Findings: The results showed that there were differences before and after the training was carried out. After the training, the ability of teachers to perform the learning evaluation process improved. Conclusion: Similarly, the responses of the teachers during the training and their perceptions of using the learning evaluation application were very enthusiastic. Research Limitations and Implications: The limitation in this study is that there are many choices in using the questions in this application so not all the model questions in the application are taught. Practical Implications: The findings of this study may be used to train instructors and raise their levels of proficiency, resulting in higher-quality human development. Contribution to the Literature: The theoretical ramifications of this research include developing appropriate modelling in training and learning through the use of direct instructional applications.